Rim-arterial enhancing primary hepatic tumors with other targetoid appearance show early recurrence after radiofrequency ablation - Cha, Dong Ik; Lee, Min Woo; Jeong, Woo Kyoung; Ahn, Soo Hyun; Kang, Tae Wook; Song, Kyoung Doo; Min, Ji Hye; Rhim, Hyunchul; Lim, Hyo Keun (European Radiology, 2021)
Objectives: To evaluate early (≤ 2 years) local tumor progression (LTP), intrahepatic distant metastasis (IDR), and extrahepatic metastasis (EM) of primary hepatic malignant tumors with arterial rim enhancement (RE) after RFA in comparison with non-RE tumors. Methods: Three hundred forty-nine patients who underwent RFA for primary hepatic malignant tumors between January 2009 and December 2016 were included. The patients’ tumors were classified into non-RE, RE only (RO), and RE plus other targetoid appearances (REoT). Cumulative LTP, IDR, and EM rates at 1 and 2 years after RFA were calculated using the Kaplan-Meier method and compared using the log-rank test. Prognostic factors for the outcomes were assessed using a Cox proportional hazards model. Results: There were 303 non-RE, 19 RO, and 27 REoT tumors. The REoT tumors had a significantly higher rate of IDR and EM than non-RE (p = 0.04 for IDR; and p < 0.01 for EM, respectively) at 1 year after RFA. At 2 years, LTP and EM rates were significantly higher for REoT than for non-RE (p = 0.001 for LTP; and p = 0.444 for EM, respectively). The RO tumors did not have different outcomes than non-RE at 1 and 2 years after RFA. Multivariable analysis verified that REoT was a significant factor for IDR (p = 0.04) and EM (p = 0.01) at 1 year and LTP (p = 0.02) at 2 years. Conclusions: Tumors with REoT had poor LTP, IDR, and EM within 2 years after RFA than non-RE tumors. However, tumors with RO showed similar results as non-RE tumors. Key Points: • Tumors with Rim enhancement plus other targetoid appearances (REoT) had a significantly higher rate of recurrence than non-rim enhancing (RE) tumors at 1 and 2 years after RFA. • Tumors with rim enhancement only did not have different outcomes than non-RE at 1 and 2 years after RFA.
Keywords: Carcinoma, Hepatocellular; Catheter Ablation; Humans; Liver Neoplasms; Neoplasm Recurrence, Local; Radiofrequency Ablation; Treatment Outcome; Carcinoma, hepatocellular; Magnetic resonance imaging; Radiofrequency ablation; Recurrence